The influence of relational marketing and e-word of mouth on Krisna Oleh-Oleh Khas Bali - I Putu Gede Arya Negara (Review of Management, Accounting, and Business Studies, 2021)
This research was conducted based on the gap in the results of previous studies (research gap) and differences in the focus of discussion about relational marketing, e-word of mouth on consumer loyalty. In addition, there are also research problems (research problems) about not achieving sales at Krisna souvenirs typical of Bali Sunset Road. This research was conducted on Krisna souvenirs typical of Bali Sunset Road with an unlimited population and the sample of this study amounted to 55 consumers. All data obtained from the questionnaire distribution are feasible to use, then analyzed using SPSS 24.0. The results of the study provide that relational marketing has a positive and significant effect on customer loyalty, e-word of mouth has a positive and significant effect on customer loyalty and relational marketing and e-word of mouth have a positive and significant effect on consumer loyalty. The implication of this research is that relational marketing can be improved by taking into account indicators of trust, reciprocity, bonding, and empathy. E-word of mouth can be improved by taking into account indicators of the willingness of consumers to talk about positive things about the company to others, recommending company services to others, and encouraging friends/relations to make purchases of company services. Consumer loyalty can be improved by taking into account indicators of regular repurchases, buying across product lines and services, recommending others, and pointing out immunity to competitors' attraction.